The Harmonization of Radon Exposure Mitigation for the Sustainability of Buildings: Assessing the Impact of the EURATOM Directive on European Legislation - Leonel J. R. Nunes; António Curado (Buildings)
Radon exposure is a major health concern associated with an increased risk of lung cancer, particularly in smokers, highlighting the need for effective mitigation measures in enclosed spaces by improving indoor air quality (IAQ), thus ensuring more sustainable buildings. The Euratom Directive, a key piece of EU legislation, sets standards for the protection of workers and the general public from ionizing radiation throughout Europe. It requires member states to implement safety measures, set exposure limits, monitor radon levels, and develop emergency plans and mitigation strategies for nuclear accidents and radiation incidents. The directive also sets reference and action levels for indoor radon. The aim of this article is to analyze the legislation on indoor radon exposure in European countries and to evaluate the impact of the directive on the standardization of the action and intervention levels. By conducting a comprehensive legislative review, this study will compare the action levels, assess the directive’s ability to harmonize the regulations, and identify legislative trends and developments. In addition, it will examine the factors contributing to the discrepancies between countries and highlight areas for improvement to ensure adequate protection against the risks of radon exposure and thereby increase the sustainability of buildings.